Optical colour image watermarking based on phase-truncated linear canonical transform and image decomposition. (18th April 2018) - Su, Yonggang; Tang, Chen; Li, Biyuan; Lei, Zhenkun
Abstract: This paper presents a novel optical colour image watermarking scheme based on phase-truncated linear canonical transform (PT-LCT) and image decomposition (ID). In this proposed scheme, a PT-LCT-based asymmetric cryptography is designed to encode the colour watermark into a noise-like pattern, and an ID-based multilevel embedding method is constructed to embed the encoded colour watermark into a colour host image. The PT-LCT-based asymmetric cryptography, which can be optically implemented by double random phase encoding with a quadratic phase system, can provide a higher security to resist various common cryptographic attacks. And the ID-based multilevel embedding method, which can be digitally implemented by a computer, can make the information of the colour watermark disperse better in the colour host image. The proposed colour image watermarking scheme possesses high security and can achieve a higher robustness while preserving the watermark's invisibility. The good performance of the proposed scheme has been demonstrated by extensive experiments and comparison with other relevant schemes.